2019
DOI: 10.1002/app.47786
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of poly(l‐lactide)/ZnO nanocomposites with antimicrobial activity

Abstract: This work investigates the effect of the incorporation of zinc oxide (ZnO) nanoparticles within a poly(L-lactic acid) (PLLA) matrix as an approach to speed up the hydrolysis of PLLA film surfaces. Hydrolysis was done by immersing nanocomposite films having 1 wt % of ZnO in 0.25 M sodium hydroxide at 58 C. This concentration has been selected as it provides the maximum changes of physicochemical properties of hosting PLLA matrix. The evolution of the thermal properties, ultraviolet-visible transparency, wettabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
2
0
2
Order By: Relevance
“…A mechanism for the hydrolytic degradation of antimicrobial PLA/ZnO nanocomposites, in phosphate buffered or in NaOH solutions, has been proposed. 75 Analogously to the above literature, the Zn centres were hypothesized to act as Lewis acid activators of the carbonyl ester bond, which then undergoes a nucleophile attack by water. In another report, it was suggested that the hydrolysis of PLA/ZnO nanocomposites occurs via anchoring of the acid end groups of PLA on a hydroxylated ZnO surface, followed by attack of the ester bond by hydroxyl anions.…”
Section: Resultsmentioning
confidence: 89%
“…A mechanism for the hydrolytic degradation of antimicrobial PLA/ZnO nanocomposites, in phosphate buffered or in NaOH solutions, has been proposed. 75 Analogously to the above literature, the Zn centres were hypothesized to act as Lewis acid activators of the carbonyl ester bond, which then undergoes a nucleophile attack by water. In another report, it was suggested that the hydrolysis of PLA/ZnO nanocomposites occurs via anchoring of the acid end groups of PLA on a hydroxylated ZnO surface, followed by attack of the ester bond by hydroxyl anions.…”
Section: Resultsmentioning
confidence: 89%
“…For polymers, it is important to ensure that the concentration and treatment duration of the acidic/alkali solution do not significantly alter the bulk properties of the underlying polymer. Additionally, in both cases, the nonspecific nature of the treatment can lead to irregular surface degradation, potentially affecting the overall surface integrity and properties of the modified material [58,79]. Therefore, careful optimization of the hydrolysis process is essential to achieve desired modifications while preserving the core properties of the substrate.…”
Section: Hydrolysis and Aminolysismentioning
confidence: 99%
“…Оксид цинка в составе остеопластического матрикса ингибирует прикрепление бактерий и стимулирует дифференцировку клеток в направлении фенотипа миоцитов [85]. При интеграции оксида в композитную систему PLLA/ZnO (ZnO в виде наностержней ~40 нм), композит медленно выделяет ионы цинка в окружающую среду [86].…”
Section: композитные каркасы с оксидами металловunclassified
“…Наностержни действуют как каталитические ядра, слегка ускоряя деградацию полимера. Это наблюдение имеет ключевое значение поскольку улучшает связь между дифференцированными миоцитами и имплантатом [85].…”
Section: композитные каркасы с оксидами металловunclassified